2010
DOI: 10.1167/10.4.25
|View full text |Cite
|
Sign up to set email alerts
|

The horizontal disparity direction vs. the stimulus disparity direction in the perception of the depth of two-dimensional patterns

Abstract: Horizontal binocular disparity has long been the conventional predictor of stereo depth. Surprisingly, an alternative predictor fairs just as well. This alternative predicts the relative depth of two stimuli from the relation between their disparity vectors, without regard to horizontal disparities. These predictions can differ; horizontal disparities accurately predict the perceived depth of a grating and a plaid only when the grating is vertical, while the vector calculation accurately predicts it at all exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…We showed that unidisparity plaids induce robust DVRs, characterized by two components: one, at very short latency, driven by the disparity of the gratings, and another, delayed by 10–15 ms, driven by the disparity in the pattern. We thus confirmed that the visual system is capable of extracting pattern disparities from plaids, as previously reported on the basis of depth perception experiments (Farell, 1998; Farell, Chai, and Fernandez, 2010; Chai and Farell, 2009; Farell, 2003). Importantly, we were able to rule out alternative interpretations, such as an effect of distortion products (Delicato and Qian, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…We showed that unidisparity plaids induce robust DVRs, characterized by two components: one, at very short latency, driven by the disparity of the gratings, and another, delayed by 10–15 ms, driven by the disparity in the pattern. We thus confirmed that the visual system is capable of extracting pattern disparities from plaids, as previously reported on the basis of depth perception experiments (Farell, 1998; Farell, Chai, and Fernandez, 2010; Chai and Farell, 2009; Farell, 2003). Importantly, we were able to rule out alternative interpretations, such as an effect of distortion products (Delicato and Qian, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…That is, the separation of stimuli within a display, in terms either of visual angle or carrier wavelengths, might have been sub-optimal for accurate coding of disparities with strongly divergent directions. However, the perceived depth separation between plaids, whether these are laterally adjacent (Farell, Chai, & Fernandez, 2010) or separated by another stimuli (Supplement Fig. S2), is consistent with a horizontal disparity metric despite a considerable difference in two-dimensional disparity direction.…”
Section: Offset and Gainsupporting
confidence: 59%
“…Suppose the plaids had disparities with equal magnitudes and orthogonal directions, +45°and À45°. They would then have equal horizontal disparities and should appear at the same depth (Farell, Chai, & Fernandez, 2010). But if the grating (oriented at, say, 135°) had a disparity that gave it the same apparent depth as one of the plaids, it should appear at different a depth from the other plaid.…”
Section: Experiments 1 Perceived Depth Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…In another condition, the target stimulus was 2-D, the same as the reference stimuli. In this case, we expect to find the perceptual depth match occurring when the target and reference stimuli have disparities with horizontal components that are equal, Attention in stereo depth judgments regardless of whether the disparity directions are parallel or perpendicular (Farell et al, 2010). For example, a pair of 2-D stimuli whose disparity directions are at +45° (where 0° is horizontal) should be seen as equal in depth when their disparity magnitudes are equal.…”
Section: Disparity Direction and Dimensionalitymentioning
confidence: 97%